2022
DOI: 10.3390/ma15020602
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Particles and Debris Released after Implantoplasty: A Comparative Study

Abstract: Titanium particles embedded on peri-implant tissues are associated with a variety of detrimental effects. Given that the characteristics of these detached fragments (size, concentration, etc.) dictate the potential cytotoxicity and biological repercussions exerted, it is of paramount importance to investigate the properties of these debris. This study compares the characteristics of particles released among different implant systems (Group A: Straumann, Group B: BioHorizons and Group C: Zimmer) during implanto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 44 publications
(75 reference statements)
0
15
0
Order By: Relevance
“…[ 17 , 23 , 24 ] Nonetheless, some instruments employed in this decontamination procedure appear to promote a large-scale release of metal particles into the surrounding tissues. [ 17 , 26 , 27 ] For example, Eger et al [ 37 ] demonstrated that the treatment of peri-implantitis using ultrasonic metal tips promoted the release of Ti particles from different implant surfaces. Moreover, the authors reported that these particles significantly increased the inflammatory and osteoclastogenic responses in vitro and in vivo , suggesting the possibility of aggravation of peri-implantitis, in short-term follow-ups (24–48 hr) and indicating the necessity of long-term examination in further studies to investigate the chronic effects of this exposure.…”
Section: Effect Of Titanium Particles and Ions On The Cellular Respon...mentioning
confidence: 99%
See 3 more Smart Citations
“…[ 17 , 23 , 24 ] Nonetheless, some instruments employed in this decontamination procedure appear to promote a large-scale release of metal particles into the surrounding tissues. [ 17 , 26 , 27 ] For example, Eger et al [ 37 ] demonstrated that the treatment of peri-implantitis using ultrasonic metal tips promoted the release of Ti particles from different implant surfaces. Moreover, the authors reported that these particles significantly increased the inflammatory and osteoclastogenic responses in vitro and in vivo , suggesting the possibility of aggravation of peri-implantitis, in short-term follow-ups (24–48 hr) and indicating the necessity of long-term examination in further studies to investigate the chronic effects of this exposure.…”
Section: Effect Of Titanium Particles and Ions On The Cellular Respon...mentioning
confidence: 99%
“…[23][24][25] However, different studies have demonstrated that decontamination techniques using burs or metal instruments, i.e., implantoplasty, generate Ti particles around the implant, which could have negative effects on bone regeneration. [26,27] As such, it must be highlighted that the concentration and size of these released particles during implantoplasty treatments are dependent on the implant chemical composition and implant surface modifications. [27] To date, the role of the released Ti particles/ions in the pathogenesis and progression of peri-implantitis is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another case leading to a large release of titanium particles into the oral environment is the technique of implantoplasty for cases of peri-implantitis. This technique consists of the mechanization of the surface of the dental implant on which a bacterial biofilm is created, whereby the mechanical removal of the infected implant surface causes a large release of particles into the oral environment [13][14][15][16]. This technique avoids the replacement of the osseointegrated implant by eliminating the infection.…”
Section: Introductionmentioning
confidence: 99%